Working memory disturbances as cognitive endophenotype markers in mental disorders: Implications for psychosocial functioning - Hintze, Beata (Studia Psychologica: Theoria et praxis, 2013)
The aim of the study was to assess working memory and executive functions in first-degree relatives of schizophrenic patients (healthy parents). There were 25 healthy parents of schizophrenic patients, 8 males and 17 females, mean age 53 years, participating in the study. The control group consisted of 25 healthy individuals, matched by age and gender to the parents of schizophrenic patients. In this group, there were 10 males and 15 females, mean age 54 years. The neuropsychological assessment included Wisconsin Card Sorting Test, N-back Test and Stroop Test. The results indicated that there were statistically significant disturbances of working memory and executive functions in the group of healthy first- degree relatives of schizophrenic patients, compared to the group of individuals unrelated to schizophrenic patients. These differences were greater in the case of parents of schizophrenics with lower level of education, compared with the healthy subjects without family history of schizophrenia.